Penggunaan hasil sensus untuk estimasi urbanisasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Abstract Urbanization can be defined in many ways: various definitions concerning it are found in population literature. Different censuses also tend to define the concept of urban differently. This inconsistency of definition has obstructed those who want to conduct a comparative analysis on , both cross-country and longitudinal analysis of a country. This article attempts to examine the problem by clarifying the definition of the concept and indicators of urbanization and by making a longitudinal analysis of urbanization using the Indonesian 1920-1990 Cencus data. Regardless of how the concept of urban is defined in each cencus, this analysis has found a steady increase in urban population number. However, it the deifferent definition of the concept are taken into consideration. it may bring up different conclution. Part of the reasons of the increase is a reclassification of village status from being rural to become urban. One way to prove this proposition is by comparing the level of urban population growth between large cities and their durrounding regencies. This analysis clearly shows that the latter has higher population growth than the former.